Serum Vitamin D Level and Carotid Intima-Media Thickness: A Systematic Review and Meta-Analysis of Observational Studies and Randomized Control Trials - Säidifard, Nasim; Tangestani, Hadith; Djafarian, Kurosh; Shab-Bidar, Sakineh (Hormone and Metabolic Research, 2020)
It is reported that vitamin D deficiency is associated with carotid intima-media thickness (CIMT). In addition, several randomized clinical trials (RCTs) have studied the influence of vitamin D supplement on CIMT. However, results are inconclusive. This review aimed to systematically explore the potential link of the serum vitamin D level with CIMT pooling together observational studies and RCTs. PubMed and Scopus were searched for studies published until February 13, 2018. The Fisher’s z (SE) correlation coefficient, odds ratio (OR), and mean (SD) of changes in CIMT from baseline were used to perform meta-analysis in observational studies and RCTs, respectively. To pool data, both a fixed-effects model and a random-effects model (in case of heterogeneity) were used. Heterogeneity was assessed using Cochran’s Q and I2 tests. Nineteen observational studies and 3 RCTs met inclusion criteria. The pooled correlation coefficients of 17 observational studies showed [(Fisher’s z=− 0.41, 95% CI: –0.63 to –0.19, p<0.001), I2=96.9%, p < 0.001] a significant inverse association between serum vitamin D and risk of CIMT. Pooling three risk estimates of three studies [(OR = 1.69, 95% CI: 0.74 to 3.86, p=0.209); I2=085.1%, p<0.001)] indicated no significant association between serum vitamin D status and risk of CIMT. Combining data of RCTs showed vitamin D supplementation significantly reduced CIMT [(MD: –0.034, 95% CI: –0.62 to –0.05, p=0.012), I2=16.6%, p = 0.301]. Our findings show that serum vitamin D is inversely associated with CIMT and vitamin D supplementation may reduce CMIT.
Keywords: vitamin D; carotid intima-media thickness; randomized clinical trials; observational; meta-analysis